Implementasi Model Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis Dalam Pembelajaran IPA Kelas 5 - Ika Putra Viratama; Ludya Fatmawati; Nabila Fitri Angelika; Rimba Rahmawati; Silvi Laila Rista Fauziah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Active and innovative learning is crucial in improving students' critical thinking skills, especially in science learning at the elementary level. The Problem Based Learning (PBL) model is an effective approach to stimulate critical thinking, analysis, and problem-solving skills in fifth-grade students. This study aims to describe the implementation of the PBL model in science learning to improve fifth-grade students' critical thinking skills. The approach used is a literature study by collecting data from various written sources such as scientific journals and relevant publications regarding the application of technology and innovative learning models. The results of this study indicate that the implementation of the PBL model can increase students' learning motivation and critical thinking skills, while also assisting teachers in creating an interesting and enjoyable learning atmosphere. Thus, the PBL model can be an effective solution in developing students' higher-order thinking competencies in an educational era that demands creativity and innovation.